ANALISIS PENGARUH PEMBEBANAN TERHADAP SUSUT UMUR TRANSFORMATOR TENAGA: STUDI KASUS TRAFO GTG 1.3 PLTGU TAMBAK LOROK, SEMARANG - Naiborhu, G. Riana (Jurnal Teknik Elektro, 2010)
Operating temperature of potential transformer design is 20 oC. However it is not applicable in Indonesia with temperature 30 oC. Because of that, the load of the transformer need to be adjusted. Operating lifetime will become shorter and loss of life will become greater at higher temperature. Loss of life of the transformer depends on winding isolation and transformer oil. Overheating in transformer winding can damage the isolation and increase oil temperature resulting in degradation of the oil. If the changes occur in a long period, it can decrease the isolation value of the oil. The final research observes the correlation between load of transformer and ambient temperature to the loss of life viewed from deterioration transformer winding insulation and analyze GTG 1.3 PLTGU Tambak Lorok Semarang Transformer loss of life refer to1972 IEC 354 standard. According the result, 80% of transformer load is caused minimum 24% loss of life. With IEC 354 standardâs transformer and 20 oC ambient temperature resulting in minimum 100% loss of life on 100% load. According to 20 load data, with maximum load of GTG 1.3 PLTGU Tambak Lorok Semarang Transformer loss of life is 15.69% Keywords: transformer, ambient temperature, loss of life